KREATIVITAS GURU DALAM MENINGKATKAN HASIL BELAJAR SISWA KELAS B PADA MASA PANDEMI RA NAWA KARTIKA DAWU TAHUN PELAJARAN 2020/2021 - Eny Setyowati; Anik Sumartin (Kurikula : Jurnal Pendidikan, 2021)
ABSTRACT The purpose of this study was to identify and describe the form of teacher creativity in an effort to improve student learning outcomes despite being constrained by the pandemic. This research was conducted at RA Nawa Kartika Dawu, precisely in the hamlet of Blimbing, Dawu Village, Paron District, Ngawi Regency. This study uses a qualitative research type with the subject studied by the teacher who teaches at RA Nawa Kartika Dawu with the methods of interview, observation, and documentation. The results of the teacher's creativity research in Improving the Learning Outcomes of Class B Students during the Pandemic Period of RA Nawa Kartika Dawu for the 2020/2021 academic year showed that it was in accordance with the Emergency Curriculum Guide for Madrasahs based on the Decree of the Director General of Islamic Education Number 2791 of 2020. While the form of teacher creativity in improve student learning outcomes of class B actualized on learning strategies, methods applied and learning media used Key Words: Teacher Creativity, Learning Outcomes, Covid-19 Pandemic.